Covid-19 Pandemic as Force Majeure: Its Enforceability on the Failure to Fulfill Contractual Obligations in Letter Of Credit - Kusumawardhani, Bhuwana Fairuz (Yustisia, 2021)
The performance of contractual obligations holds an important role in the fulfillment of sales contracts, therefore, each parties involved would done their best to complete them. The existence of COVID-19 pandemic affected the trade sphere and could bring impediment in the form of force majeure. This research aims to find out the enforceability of COVID-19 as force majeure on the performance of sales contract and the enforceability of COVID-19 as force majeure according to UCP 600 on failure to presents complying documents. This research was conducted by using normative method and qualitative method, the latter was used to analyze the secondary data of which was collected by literature study of relevant materials. The result of this research shows that the enforceability of COVID-19 as force majeure depends on the way of sales contracts are worded and the tribunal’s interpretation on the laws and practices in international trade. The UCP 600’s force majeure clause phrasing open up the interpretation on the possibility of COVID-19 as force majeure, however, the clause cannot be enforced on the failure to presents complying documents, caused by COVID-19 or not, as it concerns the matter of Bank’s responsibility in the case of force majeure